2022
DOI: 10.3390/medicina58121859
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for the Prognosis of Alcoholic Liver Cirrhosis

Abstract: Alcoholic liver cirrhosis (ALC) is a disease with multiple complications and is associated with poor prognosis and significant mortality. Identifying risk factors associated with a poor outcome is important to ensure effective treatment and increase life expectancy. We aimed to evaluate the predictive values of complications regarding mortality in ALC. We retrospectively analyzed 1429 patients with ALC hospitalized between January 2019 and April 2022 at the Institute of Gastroenterology and Hepatology Iasi. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…We found that a duration of cirrhosis of five years or longer was associated with the occurrence of PVT in our study. This observation is in line with a study by Trifan et al, which reported an increasing cumulative incidence of cirrhosis over the years following the initial diagnosis [ 22 ]. However, the assessment of the duration of cirrhosis at the time of presentation is challenging due to the largely asymptomatic nature of compensated cirrhosis.…”
Section: Discussionsupporting
confidence: 92%
“…We found that a duration of cirrhosis of five years or longer was associated with the occurrence of PVT in our study. This observation is in line with a study by Trifan et al, which reported an increasing cumulative incidence of cirrhosis over the years following the initial diagnosis [ 22 ]. However, the assessment of the duration of cirrhosis at the time of presentation is challenging due to the largely asymptomatic nature of compensated cirrhosis.…”
Section: Discussionsupporting
confidence: 92%
“…Our results support the idea that there are major differences regarding the impact of alcohol on health depending on the type of preferred drink and the particularities of consumption (moderate versus excessive), which are objectified by the abnormal changes of specific biomarkers for inflammatory status and oxidative stress. Early detection of liver fibrosis through TE could prevent the development of complications and the evolution towards alcoholic liver disease and cirrhosis that have a strong socio-economic impact on patients and healthcare systems, an idea highlighted in a study conducted by Trifan et al in which from over 1429 patients diagnosed for the first time with alcoholic liver cirrhosis during two and a half years, more than 20.8% deceased due to decompensation of the hepatic disease [45]. Improving compliance and applying monitoring strategies, specific therapy, and psychological counseling could contribute to a better prognosis for these patients.…”
Section: Discussionmentioning
confidence: 99%